2019
DOI: 10.17140/prrmoj-5-139
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Gemcitabine-Induced Pulmonary Hypertension

Abstract: Gemcitabine is the backbone of systemic treatment of locally advanced and metastatic intrahepatic cholangiocarcinoma. In recent literature, gemcitabine has been linked to various pulmonary side effects. Case Report We report a case of an 82-year-old male who developed acute pulmonary hypertension after receiving one cycle of gemcitabine for metastatic cholangiocarcinoma. His symptoms began with fatigue associated with shortness of breath and cough that worsened despite dose reduction. He developed new onset bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Although a recent study has reported no difference in LRG levels between healthy individuals and patients with UC [14], certain factors, such as age, sex, and BMI, could affect LRG values. A previous study demonstrated an association between CRP and fecal calprotectin levels and age, sex, and BMI [15][16][17][18][19]. Since we could not perform adjustments based on these variables in our analysis due to insufficient data, further data collection is necessary for a better understanding of the effects of the factors affecting LRG.…”
Section: Discussionmentioning
confidence: 97%
“…Although a recent study has reported no difference in LRG levels between healthy individuals and patients with UC [14], certain factors, such as age, sex, and BMI, could affect LRG values. A previous study demonstrated an association between CRP and fecal calprotectin levels and age, sex, and BMI [15][16][17][18][19]. Since we could not perform adjustments based on these variables in our analysis due to insufficient data, further data collection is necessary for a better understanding of the effects of the factors affecting LRG.…”
Section: Discussionmentioning
confidence: 97%
“…Only four cases of PAH have been so far published in the literature, including two cases of PVOD ( table 3 ). In 2019, S hen et al [ 19 ] reported a case of gemcitabine-induced PAH in which the patient presented with PAH following a course of gemcitabine for metastatic cholangiocarcinoma. The diagnosis was suggested by transthoracic echocardiography (TTE) in view of suggestive clinical features.…”
Section: Discussionmentioning
confidence: 99%
“…The median delay from first and last gemcitabine injection to diagnosis of PAH were 7 (4-50) and 1 (0,5-16) months, respectively. The median number of total chemotherapy injections was 16 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24), with a usual gemcitabine dose of 1000 mg/m 2 . At the time of PH diagnosis, 5 patients (55%) had a partial response to treatment or were in remission, 3 patient (33%) had tumor progression and one patient (11%) had stable neoplastic disease.…”
Section: Gemcitabine Exposurementioning
confidence: 99%
See 1 more Smart Citation